Computer-assisted recitation program: A focused study on students’ conceptual understanding on force and motion - Muhammad Reyza Arief Taqwa; Mohammad Mubarrak Mohd Yusof; Irvany Nurita Pebriana; Achmad Misbakhussuduri (Momentum: Physics Education Journal, 2023)
Recitation programs have been developed and tested on the topic of force and motion. The program consists of 63 multiple choice questions with feedback made in 3 packages (one package each week). This study aims to analyze the effectiveness of the program. This research is a quantitative research with a quasi-experimental design. The applied experimental design is a one group pretest-posttest design. The program was given for 3 weeks by giving 1 recitation package at each meeting (there are 21 questions for every package). The study was conducted on 38 Physics Education students’ who enrolled the Material and Learning Physics I course. The pretest-posttest questions consisted of 15 reasoned multiple-choice questions. Data analysis was performed by determining descriptive statistics, paired sample t-test, N-gain, and d-effect size. The research found that the program significantly improved students’ conceptual understanding with N-gain of 0.498 and d-effect size of 1.559. These results indicate that the provision of recitation programs can improve students' conceptual understanding on force and motion, especially in determining the F(t) graph from the v(t) graph, where initially the ability to solve problems in the form of graphical representations is one of the difficult matters for students.